2016
DOI: 10.1002/app.43491
|View full text |Cite
|
Sign up to set email alerts
|

Soluble asymmetric bismaleimide with low molten viscosity and its high glass transition temperature polymer

Abstract: Three novel bismaleimide monomers (MBA-BMI, EBA-BMI, and PBA-BMI) with unsymmetrical backbone and different pendant groups were synthesized using asymmetric diamine and maleic anhydride as the precursors. The prepared bismaleimide monomers show good solubility in common organic solvents such as acetone and tetrahydrofuran. The EBA-BMI melt treated at 180 8C also shows low viscosity about 190-934 mPa s at the temperature range of 160-139 8C below its melting point (166 8C). In addition to the good processabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…At the same time, the weight loss of cured resins between 500 and 800°C was decreased with increasing the content of Card‐PEPA. This can be due to Card‐PEPA has fluorene groups and more phenyl group, and it is helpful to forming carbon residue for the aromatic groups …”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the weight loss of cured resins between 500 and 800°C was decreased with increasing the content of Card‐PEPA. This can be due to Card‐PEPA has fluorene groups and more phenyl group, and it is helpful to forming carbon residue for the aromatic groups …”
Section: Resultsmentioning
confidence: 99%
“…prepared three asymmetric bismaleimides with ether linkages and 1,3,4‐oxadiazole, which showed good solubility in acetone. Our previous work also showed that the unsymmetrical chemical structure, ether linkage, and pendent groups are beneficial to the processability of BMI. For example, the asymmetric 2‐(4′‐maleimido)phenyl‐2‐(4′‐maleimidophenoxyl)phenylbutane (EBA‐BMI), as shown in Scheme , exhibited good solubility, low molten viscosity, and excellent thermal properties.…”
Section: Introductionmentioning
confidence: 88%
“…2,2‐ Bis (4‐cyanatophenyl)propane (BADCy) was supplied by Shanghai Huifeng Trade Co., Ltd. Diallylbisphenol A (DBA) was purchased from Honghu City Shuangma New Materials Tech Co., Ltd. BADCy and DBA were used as received without further purification. 2‐(4′‐Maleimido)phenyl‐2‐(4′‐maleimidophenoxyl)phenylbutane (EBA‐BMI) was synthesized according to the literature …”
Section: Methodsmentioning
confidence: 99%
“…For example, the long-time working temperature of 2,2 0 -diallylbisphenol A modified DDM-BMI is lower than 250 C, which is much less than that of PMR polyimides (>300 C). 24 The previous research revealed that due to the asymmetric structure, 2-(4 0 -maleimido)phenyl-2-(4 0 -maleimidophenoxyl)phenylbutane (EBA-BMI, Figure 1) exhibits attractive melting performance and high T g over 400 C, 25 which is comparable to that of DDM-BMI. According to the principle that the similar substance is more likely to be dissolved by each other, bis(4-maleimidophenyl)methane, 1,5-bismaleimidotoluene (30%), and 1,6-bismaleimido-2,2 0 -dimethyl-4-methylhexane (15%) with two maleimide groups in their molecular structure were successfully blended to produce a eutectic mixture, which displays low viscosity at 110 C. 7 Hence, EBA-BMI and DDM-BMI are also expected to show a good compatibility in their binary mixed bismaleimides.…”
Section: Introductionmentioning
confidence: 97%